Pengaruh Rasio Profitabilitas dan Rasio Leverage Terhadap Manajemen Laba - Desi Anggraini Sitorus; Adanan Silaban (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to examine the effect of profitability and leverage on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The independent variables in this study are profitability (Return on Assets) and leverage (Debt Equity Ratio). The dependent variable in this study is earnings management as measured by decisional accruals. Through sample selection using purposive sampling method, a total of 35 companies were obtained as objects of research and a sample of 105 observations. The data analysis technique used in this study is multiple linear regression analysis using the SPSS version 20 computer program. The results of this study indicate that profitability has a positive and significant effect on earnings management, while leverage has no effect on earnings management.